Towards global control of parasitic diseases in the Covid-19 era: one health and the future of multisectoral global health governance : chapter one - Ung, Lawson; Stothard, J. Russell; Phalkey, Revati; Azman, Andrew S.; Chodosh, James; Hanage, William P.; Standley, Claire J. (Advances in parasitology, 2021)
Human parasitic infections—including malaria, and many neglected tropical diseases (NTDs)—have long represented a Gordian knot in global public health: ancient, persistent, and exceedingly difficult to control. With the coronavirus disease (Covid-19) pandemic substantially interrupting control programmes worldwide, there are now mounting fears that decades of progress in controlling global parasitic infections will be undone. With Covid-19 moreover exposing deep vulnerabilities in the global health system, the current moment presents a watershed opportunity to plan future efforts to reduce the global morbidity and mortality associated with human parasitic infections. In this chapter, we first provide a brief epidemiologic overview of the progress that has been made towards the control of parasitic diseases between 1990 and 2019, contrasting these fragile gains with the anticipated losses as a result of Covid-19. We then argue that the complementary aspirations of the United Nations Sustainable Development Goals (SDGs) and the World Health Organization (WHO)’s 2030 targets for parasitic disease control may be achieved by aligning programme objectives within the One Health paradigm, recognizing the interdependence between humans, animals, and the environment. In so doing, we note that while the WHO remains the preeminent international institution to address some of these transdisciplinary concerns, its underlying challenges with funding, authority, and capacity are likely to reverberate if left unaddressed. To this end, we conclude by reimagining how models of multisectoral global health governance—combining the WHO's normative and technical leadership with greater support in allied policy-making areas—can help sustain future malaria and NTD elimination efforts.
Available online 11 October 2021
Version of record 22 October 2021
Gesehen am 09.05.2022